Controller Performance Assessment of a Photovoltaic Generator Terminated in a Current-Mode-Buck-Convertor-Load - Sitbon, Moshe; Mellincovsky, Martin; Aharon, Ilan (Elektronika ir Elektrotechnika, 2019)
In this paper, a comprehensive control analysis is presented, with emphasis on regulating the terminal voltage of a photovoltaic generator, interfaced with a current mode controlled buck DC-DC converter, which is, in turn terminated by a battery. The combined generator-convertor-load system possesses nonlinear behaviour, and is subject to environmental conditions, thus causing the control task complicated. Additionally, analyses of small signal equations reveal a possible unstable condition. Hence, a new method of designing a controller for worst-case scenario is presented. Additionally, results of implementing a typical linear controller (PI), which can be designed only in reference to a single nominal operation point, revealing a varied responses. Simulation and results of mathematical analysis are presented to verify the proposed method.